Telenursing Intervention for Pulmonary Tuberculosis Patients - A Scoping Review - Shalahuddin I; Pebrianti S; Eriyani T; Maulana I (Journal of Multidisciplinary Healthcare, 2024)
Iwan Shalahuddin,1 Sandra Pebrianti,2 Theresia Eriyani,3 Indra Maulana4 1Department of Community of Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 2Department of Medical Surgical Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 3Department of Basic Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, Indonesia; 4Department of Psychiatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Sumedang, Jawa Barat, IndonesiaCorrespondence: Indra Maulana, Department of Psychiatric Nursing, Faculty of Nursing, Universitas Padjadjaran, Jl. Raya Ir. Soekarno KM. 21, Hegarmanah, Jatinangor, Sumedang, West Java, 45363, Indonesia, Tel/Fax +62 (022) 7795596, Email keperawatan@unpad.ac.id; indra.maulana@unpad.ac.idAbstract: Management of care for people with Pulmonary TB at home using Information and Communication Technology (ICT) tools and innovative approaches, such as tools for telecommunications online education. In the nursing sector, the use of telecommunications is called telenursing. The purpose of this study is to determine the types of telecommunications-based interventions, especially telenursing, in monitoring the level of treatment adherence in patients with pulmonary TB. This study used a scoping review method approach to determine the type of telecommunications-based interventions, especially telenursing, in monitoring the level of treatment adherence in patients with pulmonary TB. Literature distribution using several sources, namely EBSCOhost, Scopus (Elsevier), and PubMed. To facilitate obtaining appropriate literature, PICO techniques are used in conducting literature searches, P (population/problem/patient), I (intervention, prognostic factor, exposure), C (comparison, control), and O (outcome). Keywords used in English “Tuberculosis OR Pulmonary Tuberculosis AND Telehealth OR Telehealth Nursing AND Medication Adherence OR Medication Compliance OR Behavior”. In total from the 13 articles obtained, the articles used several telehealth to pulmonary TB patients with various implementations, such as the Directly Observed Therapy, Short Course (DOTS) (n = 7). These four implementations have the same goal and support adherence to taking medication and daily recovery in pulmonary TB patients. Overall characteristics of pulmonary TB patients in the reviewed articles are pediatric TB patients (0– 14 years), adult TB (18– 30 years). A total of 9 studies used a sample population of adult TB patients (18– 30 years), TB undergoing Directly Observed Treatment Short-course (DOTS), TB receiving medical care and TB patients actively receiving treatment. The most influential effectiveness of telehealth in helping the treatment process of Pulmonary TB patients is Directly Observed Treatment Short-course (DOTS) because the main focus of the DOTS strategy is patient discovery and cure, priority is given to infectious TB patients without ruling out other types of TB.Keywords: effectiveness, intervention, pulmonary tuberculosis, telenursing, DOTS